Promoting sustainable health and safety in post-pandemic disaster risk management in Istanbul, Turkey - Agboola, Oluwagbemiga Paul (Frontiers in Built Environment, 2025)
In line with Sustainable Cities and Communities (SDG 11), the COVID-19 pandemic has exposed the vulnerabilities of urban environments, emphasizing the critical need for robust strategic planning. Effective strategies are essential for mitigating the impacts of pandemics, enhancing the city’s resilience, and safeguarding the wellbeing of city inhabitants. Thus, more strategic measures are needed to ensure the health and safety of urban populations for future occurrences. This empirical study explores how environmental planning practices can mitigate health risks, especially in the post-COVID-19 pandemic era in Turkey. The study objectives include i) investigating factors influencing the built environment and the reduction of public health risks in the wake of the COVID-19 pandemic, and ii) exploring adaptable methods to improve the built environment in the wake of the COVID-19 pandemic. The results of the responses were assessed through Structural Equation Modeling (SEM) analysis of the SmartPLS four program. Results indicated positive path significant values of <0.005 to build community resilience after the post-COVID-19 pandemic. Other significant factors include sustainable built environment practices; Public Health risks, Sustainable City Planning; and Public Health improvement strategies. The positive relationships suggest that these factors are critical in promoting a sustainable COVID-19 pandemic-free built environment in the future. Findings emphasize the importance of incorporating these significant variables into environmental planning and design as a strategy to achieve improved public health and an adaptable built environment.